Testing the Perturbation Sensitivity of Abortion-Crime Regressions - Michał Brzeziński; Maria Halber (Contemporary Economics, 2012)
The hypothesis that the legalisation of abortion contributed significantly to the reduction of crime in the United States in 1990s is one of the most prominent ideas from the recent 'economics-made-fun' movement sparked by the book Freakonomics. This paper expands on the existing literature about the computational stability of abortion-crime regressions by testing the sensitivity of coefficients' estimates to small amounts of data perturbation. In contrast to previous studies, we use a new data set on crime correlates for each of the US states, the original model specifica-tion and estimation methodology, and an improved data perturbation algorithm. We find that the coefficients' estimates in abortion-crime regressions are not computationally stable and, therefore, are unreliable.
Keywords: C52; J13; K42; 330; abortion; crime; computational stability; perturbation test